EXPERIMENTAL STUDY ON THE PHENOMENA ON THE SUCCESSIVE DROPLETS IMPACTING HOT COPPER SURFAC - Arif Widyatama; Akmal Irfan Majid; Teguh Wibowo; Deendarlianto Deendarlianto; Samsul Kamal (Jurnal Penelitian Saintek, 2019)
This study was aimed at investigating the phenomena and interactions between water droplets and hot metal surfaces using an experimental method. In this study, the droplet was dropped from 50 mm from the top of the metal surface with a frequency of 8.5 droplets per second. The observed droplet diameter was 3.12 mm. The metal used was copper with a surface temperature between 110-240 ° C. High speed video camera with a speed of 2000 fps was used to record visual data. Then the image processing technique was applied to calculate the change in droplet diameter. The results show that at low temperatures, droplets tend to maintain their initial position of contact with fluctuating deformations. While at high temperatures, a bounce phenomenon occurs which results in collisions between droplets being imperfect. Visualization results can reveal the complete change in the droplet geometry in the form of spreading ratio and complete apex height. The temperature of 140° C is the initial transition area for phenomena that result in droplets has no contact with hot surfaces so that the process of heat transfer between surfaces is inhibited.STUDI EKSPERIMEN PADA FENOMENA SUCCESSIVE DROPLETS MENUMBUK PERMUKAAN TEMBAGA PANASPenelitian ini bertujuan untuk mempelajari fenomena dan interaksi antara tetesan air (droplet) dan permukaan logam panas dengan metode eksperimental. Pada penelitian ini, droplet dijatuhkan dari posisi 50 mm dari atas permukaan logam dengan frekuensi 8,5 droplet per detik. Diameter droplet yang diamati sebesar 3,12 mm. Logam yang digunakan adalah tembaga dengan temperatur permukaan di antara 110-240° C. High speed video camera dengan kecepatan 2000 fps digunakan untuk merekam data visual. Teknik image processing diaplikasikan untuk menghitung perubahan diameter droplet. Hasil penelitian menunjukkan bahwa pertama, pada temperatur rendah, droplet cenderung mempertahankan posisi awal kontak dengan perubahan bentuk yang fluktuatif. Kedua, temperatur tinggi, terjadi fenomena bouncing yang mengakibatkan tumbukan antar droplet menjadi tidak sempurna. Hasil visualisasi dapat mengungkap perubahan geometri droplet berupa spreading ratio dan apex height secara lengkap. Dari penelitian ini juga diketahui bahwa temperatur 140°C menjadi daerah transisi awal terjadinya fenomena yang mengakibatkan droplet tidak bersinggungan dengan permukaan panas sehingga proses perpindahan kalor antar permukaan terhambat.